‘It is scary to pause treatment’: perspectives on HIV cure-related research and analytical treatment interruptions from women diagnosed during acute HIV in Durban, South Africa: Socio-Behavioral research - Deli Mthimkhulu; Krista L. Dong; Mzwakhe Wiseman Ngcobo; Deborah Mindry; Ayanda Zulu; Ntombifuthi Langa; Luyanda Maphalala; Vanessa Pillay; Maud Mthembu; Annie Miall; Whitney Tran; Ana Dillen; et al. (HIV Research & Clinical Practice, 2025)
Background HIV remains a major challenge in KwaZulu-Natal, South Africa, particularly for young women who face disproportionate risks and barriers to prevention and treatment. Most HIV cure trials, however, occur in high-income countries. Objective To examine the perspectives of young women diagnosed with acute HIV in a longitudinal study, focusing on their perceptions on ATI-inclusive HIV cure trials and the barriers and facilitators to participation. Materials and Methods Between October 2022 and February 2024, we conducted closed-ended surveys and in-depth interviews with 20 women aged 19–33 living with HIV, who were willing but ineligible or unable to participate in an HIV cure trial. Results Many participants reported mental health challenges, including major depression (40%), moderate to severe anxiety (35%), and low self-esteem (35%). While women diagnosed during acute HIV supported pausing antiretroviral treatment (ART) during analytical treatment interruption (ATI) to advance HIV cure research, concerns about health risks and HIV-related stigma were significant barriers to enrollment. Trust in the research team and close monitoring were seen as positive factors, while fears around sharing of HIV/ATI status and transmission to sex partners complicated decision-making. Participants expressed a need for psychological counseling and access to community resources to manage ATI-related stressors. Conclusions Understanding women’s perspectives on HIV cure research, especially ATI trials, is vital. Building trust and addressing psychosocial challenges through a healing-centered approach can facilitate trial participation. Socio-behavioral research before and during HIV cure trials will be essential to inform participant-centered protocol design.